Impact of Climate Change on the Density Altitude of Nine Chinese Airports - Ting Xu (Forest Chemicals Review)
The development of civil aviation has an impact on global climate change, and climate change will also affect the operation of civil aviation. In civil aviation, density altitude is a physical quantity used to measure aircraft performance. The higher the density altitude, the worse the aircraft performance and control efficiency. In the present work, ERA-Interim data and the output of 18 global climate models in CMIP6 were used to investigate the impact of climate change on the density altitude of nine airports in China. Historical data show that during the period 1979–2014 the density altitude of these nine airports exhibited an increasing trend, and most increased faster in spring and summer. Kace-1.0-G is the best model to simulate the historical trend of 18 global climate models, and is better than the multi-model ensemble. Using the output results of the Kace-1.0-G model under three different scenarios (SSP2-4.5, SSP3-7.0, and SSP4-8.5), the future projection of the density altitude of the nine Chinese airports in question was studied. Results show that the density altitudes of all nine airports exhibit an increasing trend from 2015 to 2100, and the higher the emission scenario, the greater the increase. Nonetheless, the model predicts that density altitude at most airports will increase faster in the winter, unlike under historical conditions.